Green synthesis of iron and nitrogen co‐doped porous carbon via pyrolysing lotus root as a high‐performance electrocatalyst for oxygen reduction reaction. (20th February 2021) - Zhong, Guoyu; Xu, Mengjie; Xu, Shurui; Fu, Xiaobo; Liao, Wenbo; Xu, Yongjun
Summary: Carbon‐based oxygen reduction reaction (ORR) catalysts, especially N‐doped carbon and Fe/N co‐doped carbon (Fe‐N‐C) catalysts are the most promising substitution for Pt‐based catalysts. However, most preparations of carbon‐based ORR catalysts consume large amounts of fossil organic nitrogen compounds and high‐cost carbon supports. Herein, this paper reports a green strategy employing nontoxic CaCl2 as an activating agent, FeCl3 as a metal source, and urea as a nitrogen source to synthesize iron and nitrogen co‐doped porous carbon from lotus root. The as‐synthesized lotus root‐derived carbon (L1221‐90) is featured by high specific surface area (899.90 m 2 g −1 ), abundant pores, highly disperse FeN x, and doped‐N. The optimal L1221‐900 respectively exhibits a high selectivity 4e − ORR route with high half‐wave potential of 0.960 and 0.660 V in alkaline and acid medium, which is proximate to commercial Pt/C. It is found that graphitic‐N and FeN x are the possible active sites, while abundant pores, especially the mesoporous, facilitate the O2 diffusion. Theoretical calculations reveal that the FeN x with different coordination numbers displays different ORR activities in acid medium. The L1221‐900 presumably contains some slightly active FeN x species, which leads to the relatively lower ORR activity in the acid medium. This research develops a green approach to prepare Fe‐N‐C catalyst for ORR. Abstract : Lotus root‐derived carbon Fe/N co‐doped porous carbon was synthesized through one‐pot CaCl2 activation. In 0.1 M KOH, the lotus root‐derived carbon exhibits a high selectivity for 4e − ORR route and slightly better activity than commercial Pt/C catalyst with the help of superior properties such as high specific surface area, abundant mesopores, and highly active FeN x sites.